Medium. The final season [7] [videorecording (DVD)] - Arquette, Patricia, 1968-; Weber, Jake, 1964-; Sandoval, Miguel, 1951-; Carabello, Madison, 2002-; Carabello, Miranda, 2002-; Cubitt, David, 1965-; Lark, Maria, 1997-; Vassilieva, Sofia, 1992-; DuBois, Allison (Paramount Home Entertainment, 2011)
Allison Dubois is a strong-willed, devoted young wife and mother of three girls, who has gradually come to grips with her extraordinary ability to talk to dead people, see the future in her dreams, and read people's thoughts. This season, Allison and her family's world is turned upside down after her abilities are publicly exposed, resulting in sweeping changes both professionally and personally.